Can Democracy Help the Almajiri Child in Nigeria? - Charles, Alfred; Osah, Goodnews (NIU Journal of Social Sciences; Vol 4 No 4 (2018): KIU Journal of Social Sciences, Vol. 4 No. 4, December 2018, 2019)
The all-round anguish an average Almajiri child is suffering in Nigeria has attracted sharp interrogations: internationally and otherwise. The fact that the age-old almajiranci system needs a life-saving reformation is a point that have been made severally by certified child rights activists, the past and current governors of the northern states and the religious authorities. The believe, that, democracy and its â€œfall-outsâ€, which was recently ushered in as a governance system in 1999 will help to revitalize the almajiranci system towards the liberation of the victims, the children and the adolescents, is still a gospel truth to some authorities. Hence, it was the core focus of this study to interrogate this belief, the trust that, ordinarily and inherently, democracy has the wherewithal to positively help the Almajiri child in Nigeria. The interrogations that were done to answer the central question were done through a comprehensive analysis of the salient tenets of democracy vis-Ã -vis it Nigerian brand. The study concluded that, until Nigeria decides to practice a kind of welfare democracy that will jettison some extreme capitalistic components of the democracy it is currently practicing, the Almajiri system will be the lot of the nation for a long time. Keywords: Almajiri, almajiranci, democracy, governance and Nigeria.